Price discovery and learning during the German 5G auction - Thomas Dimpfl; Alexander Reining (Journal of Risk and Financial Management, 2021)
The auctioning of frequency has to comply with a multitude of requirements in order to guarantee a transparent and efficient process. The German Federal Network Agency (Bundesnetzagentur) has opted for a design that provides participants with information on the highest bid after each round for every band along with information on the bidder. We evaluate the price formation efficiency in this setup to see how fast prices become informative about the final auction value. We find that prices are partially informative right from the beginning which allows us to conclude that participants were able to learn fast from their competitors' bidding behavior and validates the choice of the agency to implement the auction in the present format.
Keywords: C58; D44; L96; 330; 5G auction; learning; price formation